2020
DOI: 10.2147/idr.s283999
|View full text |Cite
|
Sign up to set email alerts
|

<p>COVID-19 Knowledge, Attitudes, and Prevention Practices Among People with Hypertension and Diabetes Mellitus Attending Public Health Facilities in Ambo, Ethiopia</p>

Abstract: Background: To confirm effective preventive practice and reduce the risk of COVID-19 data on knowledge, attitude, and preventive practices (KAP) are essential. Therefore, the current study was designed to evaluate the KAP of COVID-19 among people with hypertension (HTN) and/or diabetes mellitus (DM) attending public health facilities in Ambo town. Patients and Methods: Institutional-based cross-sectional study design was done among patients with HTN and/or DM from June 2020 to September 2020 at Ambo University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
46
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 28 publications
5
46
3
3
Order By: Relevance
“…In addition to this, a study conducted among diabetes mellitus and hypertensive clients attending public health facilities in Ambo shows that 10.4% of study subjects had good COVID-19 prevention practice measures which are very low as compared to our study finding. 16 Besides this, a study in Debre Tabor General Hospital, Ethiopia, showed that about 49.0% have good prevention practice towards COVID-19 which is higher than the finding of this study. 17 However, 60.8% of study subjects in Cameron showed that good preventive practice for COVID-19.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In addition to this, a study conducted among diabetes mellitus and hypertensive clients attending public health facilities in Ambo shows that 10.4% of study subjects had good COVID-19 prevention practice measures which are very low as compared to our study finding. 16 Besides this, a study in Debre Tabor General Hospital, Ethiopia, showed that about 49.0% have good prevention practice towards COVID-19 which is higher than the finding of this study. 17 However, 60.8% of study subjects in Cameron showed that good preventive practice for COVID-19.…”
Section: Discussioncontrasting
confidence: 66%
“…Again this was supported by the finding from a study done among Chronic Patients at Addis Zemen Hospital, Ethiopia. 16 Similarly, a study conducted among diabetic and hypertensive clients visiting community health facilities in Ambo, Ethiopia indicates that those who do not have formal education were associated with poor prevention practice. 16 …”
Section: Discussionmentioning
confidence: 99%
“…A study in Sierra Leon found that social media was strongly associated with increased knowledge and avoiding crowds. 16 This was represented in several studies 21,22 that stated those with good knowledge are more likely to adopt precaution measures. Information source from the national ministry of health was also associated with increased risk perception towards…”
Section: Discussionmentioning
confidence: 99%
“…In Ambo, Ethiopia, daily access to information reduces the level of poor knowledge by 54.4%. 22 In other ways, students with higher knowledge levels have a higher risk perception of COVID-19. 23 To mitigate COVID-19 transmission, Debre Berhan University has established general rules and regulations.…”
mentioning
confidence: 99%
“…Scales must be used to fill this gap and encourage a sound awareness of COVID-19, which would aid in disease control. Behavioral improvements and positive attitudes rely primarily on the level of COVID-19 expectations and knowledge of preventive activities ( 35 ).…”
Section: Discussionmentioning
confidence: 99%